2001
DOI: 10.1507/endocrj.48.25
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Angiotensin II, Renin Activity and Serum Angiotensin-Converting Enzyme Activity in Non-Insulin Dependent Diabetes Mellitus Patients with Diabetic Nephropathy.

Abstract: Abstract.The renin-angiotensin system (RAS) has been unequivocally implicated as a mediator of diabetic complications. The present study was designed to evaluate the RAS in non-insulin dependent diabetic patients with diabetic nephropathy.Plasma renin activity, plasma angiotensin II and serum angiotensin-converting enzyme (ACE) activity were measured in 45 non-insulin dependent diabetes mellitus (NIDDM) patients and 15 healthy non-diabetic controls. Diabetics were subdivided into 15 normoalbuminuric NIDDM subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
(7 reference statements)
1
19
1
1
Order By: Relevance
“…A decrease in renin production is the likely cause of lower ANG II levels in ZO and ZDFO rats; this may be a reflection of a greater loss of renal parenchyma with the more severe levels of hydronephrosis in ZO and ZDFO rats than that seen in ZL rats. Nevertheless, the lower plasma ANG II levels are not consistent with previous reports in diabetic rats with renal dysfunction (16). Importantly, the lower ANG II levels in ZDFO rats in the face of LV dysfunction and increased plasma norepinephrine levels suggest a blunted renin-angiotensin system.…”
Section: Discussioncontrasting
confidence: 87%
“…A decrease in renin production is the likely cause of lower ANG II levels in ZO and ZDFO rats; this may be a reflection of a greater loss of renal parenchyma with the more severe levels of hydronephrosis in ZO and ZDFO rats than that seen in ZL rats. Nevertheless, the lower plasma ANG II levels are not consistent with previous reports in diabetic rats with renal dysfunction (16). Importantly, the lower ANG II levels in ZDFO rats in the face of LV dysfunction and increased plasma norepinephrine levels suggest a blunted renin-angiotensin system.…”
Section: Discussioncontrasting
confidence: 87%
“…Nicola et al 31) have reported that plasma A is lower in non-complicated T2Ds compared to healthy controls, and higher in T2Ds with nephropathy compared to non-complicated T2Ds. In this study, although pioglitazone decreased HbA1c significantly, the decrease in HbA1c did not correlate with the decrease in plasma A ; therefore, the effect of pioglitazone on decreasing plasma A may be independent of its glucose-lowering effect.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported suppressed, normal, or elevated levels of renal and plasma Ang II in diabetes [24,25,26]. Kikkawa et al [27] reported biphasic alteration of the RAS that included higher plasma renin activity and higher levels of Ang II and aldosterone in the plasma in early diabetes, while lower levels were observed 4 weeks after STZ injection.…”
Section: Discussionmentioning
confidence: 99%